What works? : evidence-based policy and practice in public services - Nutley, Sandra M.; Smith, Peter (Peter C.); Davies, H. T. O. (The Policy Press, 2000)
"What counts is what works -- but how can we actually tell what works? And what can we do with such knowledge to influence policy and practice? As all parts of the public sector embrace 'evidence' as a means of providing more effective and efficient public services, this book provides a contribution to such debates. The authors consider the role of evidence in specific public policy areas (healthcare, education, criminal justice, social care, welfare, housing, transport, and urban renewal), using experts in each field to explore the creation, dissemination, and use of evidence within each. They consider in particular: How is research evidence of service effectiveness created? How does such evidence shape policy and influence service delivery? What efforts are being made to encourage greater utilisation of evidence in policy and practice? The rich cross-sectoral accounts of the many and diverse activities in each sector provide an insight into the ebb and flow of evidence as guidance to policy and practice. The book develops perceptive analyses of outstanding problems, and raises challenging agendas for service development and future research. The authors conclude with the all-important question of the implementation of evidence-based practice."--